Collagen peptide markers for three extinct Australian megafauna species - Peters, Carli; Oertle, Annette; Gillespie, Richard; Boivin, Nicole; Douka, Katerina (Frontiers in Mammal Science, 2025)
Recent advancements in biomolecular archaeology, such as stable isotope and ancient DNA research, have expanded our understanding of megafauna extinction processes and dynamics. The rise of palaeoproteomics, specifically Zooarchaeology by Mass Spectrometry (ZooMS), has added yet another method to this toolkit, as it can be used to taxonomically identify megafauna remains amongst highly fragmented bone assemblages. However, taxonomic identifications with ZooMS are reliant on the availability of collagen peptide markers for the regional fauna of interest. In the absence of a global reference database, most studies to date have been restricted to Eurasian contexts. Here, we report ZooMS peptide markers for three extinct Australian megafauna species: Zygomaturus trilobus, Palorchestes azael, and Protemnodon mamkurra. We show that these taxa can be differentiated from extant Australian fauna with these peptide markers. This foundational work represents an important step in establishing ZooMS as a method that can be used to identify new megafauna specimens in Australia’s highly fragmented fossil record and ultimately help resolve fundamental questions related to human–fauna–environment interactions.